(untitled) (International Journal of Studies in Nursing, 2018)
Intensive care unit (ICU) nurses face many uncertain situations that may affect their patient care decisions and jeopardize patients’ safety. Aim: This study aimed to explore the relationship between uncertainty and patient safety culture among intensive care unit nurses at Tanta Main University Hospital. Study subject: included (155) nurses worked in intensive care units at Tanta University Main Hospital. Two tools were used Tool (I): Nurses’ Uncertainty Questionnaire. Tool (II): Patient Safety Culture Questionnaire. Results: 74.2% of participant ICU nurses’ experienced high levels of uncertainty. Above half (56.1% and 56.1%) of them always experienced being uncomfortable and confused& loss of control when facing uncertain situations in ICUs. 84.5% and 76.8% of them always used team work; and learn from past experience to deal with uncertainty. 47.1% of them evaluated patient safety in their ICUs as acceptable and bad. There was a high statistical negative correlation between the levels of patient safety culture and experiencing uncertainty by ICU nurses at p= 0.000. Conclusions: ICU nurses experienced high level of uncertainty; they rely on experience and teamwork rather than evidence-based practices to manage clinical uncertainty. High statistical significant negative correlation was found between patient safety culture and experiencing uncertainty by ICU nurses.